Short-Term Outcomes of Patients With COVID-19 Undergoing Invasive Mechanical Ventilation: A Retrospective Observational Study From Wuhan, China - Zhao, Shuai; Lin, Yun; Zhou, Cheng; Wang, Li; Chen, Xueyin; Clifford, Sean P.; Akca, Ozan; Huang, Jiapeng; Chen, Xiangdong (Frontiers in Medicine, 2020)
Background: COVID-19 has spread rapidly worldwide. Many patients require mechanical ventilation. The goal of this study was to investigate the clinical course and outcomes of patients with COVID-19 undergoing mechanical ventilation and identify factors associated with death. Methods: Eighty-three consecutive critically ill patients with confirmed COVID-19 undergoing invasive mechanical ventilation were included in this retrospective, single-center, observational study from January 31 to March 15, 2020. Demographic, clinical, laboratory, radiological, and mechanical ventilation data were collected and analyzed. The primary outcome was 28-day mortality after endotracheal intubation. The secondary outcomes included the incidences of SARS-CoV-2-related cardiac, liver, and kidney injury. Results: Seventy-four out of 83 (89.2%) patients achieved oxygen saturation above 93% after intubation. Forty-nine out of 83 (59%) patients died and 34 (41%) patients survived after 28 days of observation. Multivariable regression showed increasing odds of death associated with cardiac injury (odds ratio 15.60, 95% CI 4.20-74.43), liver injury (5.40, 1.46-23.56) and kidney injury (8.39, 1.63-61.41), and decreasing odds of death associated with the higher PaO2/FiO2 ratio before intubation (0.97, 0.95-0.99). PaO2/FiO2 ratio before intubation demonstrated a positive linear correlation with platelet count (r = 0.424, P = 0.001), and negative linear correlation with troponin I (r= -0.395, P = 0.008). Conclusions: Lower PaO2/FiO2 ratio before intubation, cardiac, liver and kidney injury were associated with death for critically ill patients with COVID-19 undergoing invasive mechanical ventilation. The severity of pre-intubation hypoxia was associated with a poorer outcome of patients with COVID-19 undergoing invasive mechanical ventilation. Understanding the mechanism may lead to developing effective interventions.